CEST‐MRI detects metabolite levels altered by breast cancer cell aggressiveness and chemotherapy response. (21st April 2016) - Chan, Kannie W. Y.; Jiang, Lu; Cheng, Menglin; Wijnen, Jannie P.; Liu, Guanshu; Huang, Peng; van Zijl, Peter C. M.; McMahon, Michael T.; Glunde, Kristine
Abstract : Chemical exchange saturation transfer (CEST) is an MRI contrast mechanism that detects the exchange of protons from distinct hydroxyl, amine, and amide groups to tissue water through the transfer of signal loss, with repeated exchange enhancing their effective signal. We applied CEST to detect systematically 15 common cellular metabolites in a panel of differentially aggressive human breast cancer cell lines. The highest CEST contrast was generated by creatine, myo‐inositol, glutamate, and glycerophosphocholine, whose cellular concentrations decreased with increasing breast cancer aggressiveness. These decreased metabolite concentrations resulted in turn in a decreased CEST profile with increasing breast cancer aggressiveness in water‐soluble extracts of breast cell lines. Treatment of both breast cancer cell lines with the chemotherapy drug doxorubicin resulted in increased metabolic CEST profiles, which correlated with significant increases in creatine, phosphocreatine, and glycerophosphocholine. CEST can detect breast cancer aggressiveness and response to chemotherapy in water‐soluble extracts of breast cell lines. The presented results help shed light on possible contributions from CEST‐active metabolites to the CEST contrast produced by breast cancers. The metabolic CEST profile may improve detection sensitivity over conventional MRS, and may have the potential to assess breast cancer aggressiveness and response to chemotherapy non‐invasively using MRI if specialized metabolic CEST profile detection can be realized in vivo . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Chemical exchange saturation transfer (CEST) was applied to detect 15 common cellular metabolites in a panel of differentially aggressive human breast cancer cell lines. The highest CEST contrast was generated by creatine, myo‐inositol, glutamate, and glycerophosphocholine, whose cellular concentrations decreased with breast cancer aggressiveness. These decreased metabolite concentrations resulted in turn in a decreased CEST profile with increasing breast cancer aggressiveness in water‐soluble extracts of breast cell lines. Treatment of both breast cancer cell lines with the chemotherapy drug doxorubicin resulted in increased metabolic CEST profiles, which correlated with significant increases in creatine, phosphocreatine, and glycerophosphocholine.